Physiological Response and Production of Soybean Plants (Glycine max (L.) Merril) as Affected by Salicylic Acid Application under Drought Stress Conditions - Rosyida Rosyida; Salsabila Salsabila; Susilo Budiyanto (Institut Pertanian Bogor, 2026)
Drought alters plant physiological systems, which has an additional influence on soybean yield. Salicylic acid is a biostimulant that can help plants cope with stress. The study's goal was to examine how salicylic acid foliar spray affected the physiological response and productivity of soybean plants in drought conditions. The study employed soybeans from the Grobogan variety, carried out from August to October 2022 at the Greenhouse and Laboratory of Plant Physiology and Breeding, Faculty of Animal and Agricultural Science, Universitas Diponegoro, Semarang City. The study employed a 3×3 Factorial Complete Randomized Design with three repetitions, yielding 27 experimental units. The first factor was drought stress, which had three levels (80%, 60%, and 40% field capacity). The second factor was the concentration of salicylic acid, which has three levels (0, 0.5, and 1 mM). The parameters measured included leaf chlorophyll, relative water content, stomatal density, number of flowers, fresh pod weight, dry pod weight, and number of seeds. The observation data was statistically analyzed using 5% ANOVA, followed by the Duncan multiple distance test (DMRT). A 40% field capacity drought stress treatment reduced chlorophyll levels a, b, as well as the total number of flowers, fresh pod weight, and dried pod weight. The application of salicylic acid at a dosage of 1 mM increased the fresh weight of the pods. Keywords: drought, physiological response, salicylic acid, soybean